Antioxidant activity of corncob liquid smoke and traditional to smoked milkfish (Chanos chanos Forsk) during frozen storage - Setyastuti, Aryanti Indah; Ayu, Rr. Nurina; Sarmin, Sarmin (Universitas Malikussaleh, 2022)
Smoking is the one of the efforts to maintain the quality of smoked fish. Phenol compounds in smoke can act as natural antioxidants to inhibit the lipid oxidation. Milkfish has a high lipid content after protein, that can undergo lipid oxidation during processing and storage. The aim of this study was to observe the effect of antioxidant activity on different smoking methods and storage time for 28 days at freezing temperature on the quality of smoked milkfish. Corn cob liquid smoke was used due to phenol content as an antioxidant. The design used in this study was a factorial completely randomized design which consisted of two factors. The first factor is the difference in smoking methods, corncob liquid smoke (Ac) and Traditional (Tr). While the second factor is the length of storage on day 0 (T0); day 14 (T14) and day 28 (T28). The test parameters observed were analysis of phenol content; PV; TBA; lipid content; and pH. The results of this study showed that different smoking methods and storage time at freezing temperature showed significant differences (P<0.05) on the phenol value; PV; TBA; lipid value; and pH of smoked milkfish. During storage, phenol value; lipid; and pH of smoked milkfish decreased. Meanwhile, the value of PV and TBA increased as a result of the lipid oxidation process so as to produce peroxide from detheorized fat. The PV and TBA values of smoked milkfish are still acceptable by consumers.Keywords: Antioxidant acticvity; Corncob liquid smoke; Milkfish; Traditional